Program Pendampingan Hak Kekayaan Intelektual (Merek Dagang) Untuk Pengembangan Usaha (Usaha Penggilingan Bakso Kecamatan Medan Amplas) - Sri Hidayani; Abdul Lawali Hasibuan (Universitas Medan Area, 2020)
The discussion researched in this Community Service is How the Legal Regulations in Registering Trademarks in Making Meatballs in the Bakso Milling Business in Medan Amplas District. What are the responsibilities of entrepreneurs with the ingredients used in the manufacture of meatballs that have not used the mark in Medan Amplas District. The method of community service used is juridical empirical community service, namely the service to the legal community which is carried out by directly examining the field where the object under study is conducted by conducting interviews.